Natural and anthropogenic impacts on mangrove carbon dynamics: a systematic review protocol - Gilang Qur’ani, C.; Lee, B.; Sasmito, S.D.; Maulana, A.M.; Seol, M.; Wiradana, P.A.; Leksono, B.; Watiniasih, N.L.; Baral, H. (Informa UK Limited, 2024)
The mangrove ecosystem serves as a vital habitat for coastal flora and fauna while playing a crucial role in storing and sequestering carbon as part of global carbon cycles. Therefore, it is imperative to evaluate the carbon dynamics, encompassing storage and sequestration, within mangrove ecosystems and their interconnectedness with natural climate fluctuations and anthropogenic influences, including land-use and land-cover changes (LULCC). Although there has been an increase in monitoring data and literature on mangrove carbon dynamics over the past two decades, there is still limited understanding regarding how climate variability, when combined with anthropogenic drivers, moderates the resilience of carbon storage and sequestration in mangroves. This study aims to build upon and enhance the previous systematic review conducted by Sasmito et al. (Citation2019). Our specific objectives involve collating more recent literature published since 2018 and strengthening the analysis of carbon loss and recovery in tree biomass across different species, as well as its correlation with local and regional climate variations. Additionally, we will explore the impact of various types of land-use and land-cover changes on mangrove forests. Our systematic review will focus on field-based data collected from the Asia Pacific mangrove region, which represents the world’s largest and most diverse mangrove ecosystem and has been extensively studied in comparison to other regions, as indicated by previous systematic reviews. To gather relevant literature, we will conduct comprehensive searches across various databases, including Scopus, Web of Science, and Google Scholar. The structure established by Sasmito et al. (Citation2019) for literature search, screening, and data extraction will be adopted. Data analysis will involve comparing carbon storage and sequestration under locally and regionally varying climatic conditions and anthropogenic influences. Furthermore, we will employ geographical mapping techniques to visualize species distribution and diversity within the Asia Pacific region, while also estimating carbon storage and recovery capacities.